Thermomechanical study and thermal behavior of plasticized poly (Lactic acid) nanocomposites - Zorah Mohammed (Tanjung Malim, 2021)
Thermomechanical study and thermal behavior of plasticized poly (Lactic acid) nanocomposites by Zorah Mohammed